SPACE DENSITY DISTRIBUTION OF METEOROIDS OVER THE SPHERE WITH RADIUS 1 A.U. - Belkovich, O. I.; Suleymanova, S. L. (Одеські астрономічні публікації, 2017)
Space density distributions of meteoroids over the sphere with radius 1 AU and the centre in the Sun were found for meteoroid masses greater than 10-3 g, 10-2 g and 1 g. Meteoroids with greater masses concentrate to the ecliptic plane